Incentive System in Hungarian High Performance Sport - Sterbenz Tamás; Gulyás Erika; Kassay Lili (Sciendo, 2014)
This study will attempt to describe the role of existing incentives which have a significant effect on Hungarian sport's performance. The aim of the paper is to understand why a large gap has emerged between successful elite sports and the popular but underperforming spectacular sport. According to the concept of dual competition, in addition to sport results, the analyzed fields also concern competition for resources, particularly for the attention of supporters and sponsors. The methodology of the analysis is fundamentally economic in nature; however, qualitative methods are also given emphasis, as the analyzed topic has specific characteristics. Based on new institutional economics, the study presumes that the behavior of organizations is determined by the decisions of bounded rational individuals, and highlights the significance of the created mechanisms and institutions.